If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x+2)-3=0
We simplify the equation to the form, which is simple to understand
4(3x+2)-3=0
Reorder the terms in parentheses
+(+12x+8)-3=0
Remove unnecessary parentheses
+12x+8-3=0
We move all terms containing x to the left and all other terms to the right.
+12x=0-8+3
We simplify left and right side of the equation.
+12x=-5
We divide both sides of the equation by 12 to get x.
x=-0.41666666666667
| 1.3+v=5.3 | | 5z-23=-41+32 | | 2x^2+2y^2-20x-16y-16=0 | | 2.6x+1.17-3.4=5.2 | | 6+3y-3=7y+5-5y | | 3(6x+2)-18x=12 | | 5x+3=9x+21 | | (4h+9)(h-4)=0 | | (12+5i)-(9-2i)=0 | | 1.3+5.3=24.2 | | 2(-4y+4)+8y=8 | | 9x^2-30x-525=0 | | 3r-14=-28+r | | -90=9x | | -19+x=-11 | | 5x+25+2x+15=180 | | 68=17n | | -14=n+3 | | (y-6)(9y-7)=0 | | -41-19=15a | | y^3+y^2-5y-x^2=-4 | | x+6+x+9+x+3=x | | 8a-5a-3a+a=20 | | 1=2(5-6x) | | 10v=2(9-2v) | | 11=m+20 | | 3ky-12kz+24kw=0 | | q(q+7)=0 | | 1-4p=-2(5p-1)+5 | | 2x+3y-2=5 | | -15=b-16 | | (2c-9)(c-1)=0 |